Readiness to enter working life as a registered nurse of final year nursing students in a public university - Chong, Li Tsu; Mohd Nizam Kassim; Jane Ivanna Joss; Nurisrahwati Arif; Sherilviana Jukilin (Malaysian Journal of Medicine and Health Sciences, 2020)
The final year of the study period is the time students should be in the mood of ready to enter working life. There are concerned that newly graduated nurses do not have the necessary skills and competence once they enter the working life. The final year nursing students seldom have confidence because they were not getting enough experience in the clinical posting. The soft skill and not being able to perform in the clinical area and their readiness to work in real working life. Thus, this study is to assess final year and newly graduated students’ readiness to enter the real working life environment after graduated from the institution. Methods: This study using cross-sectional sur¬vey design using convenience sampling method. Adapted questionnaire is used and distributed via on-line Google form to all final year nursing and newly graduated of nursing students Universiti Malaysia Sabah. Results: Total 71 respondents (63.38% third-year and 21.12% newly graduated students) responded to this survey. 68 students (95%) were ready to enter the real working life and there were two students (5%) that still not ready to perform on their own after the course finished. Majority 70 (98.59%) find that early exposure to a real working environment was important to polish student soft skill and enhance student performance skill in doing any procedure. 96% responded that early exposure will develop student competency in leadership qualities to guide their teamwork and adaptation from the real scenario on how they will perform in their work in the future. Complete facilities in the practical area can make the student feel excited to start working in clinical area is the possible factor rated in more than half of the responded (57.7%). Conclusion: Most of the participant is ready to apply their knowledge and skill in a real working situation.